Formation of Professional Competencies in the Prospective Agronomy Research Workers - Antipova, Nataliia; Antipov, Ihor (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
The article specifies the content and structure of the professional training of masters-agronomists in selective breeding and genetics, and sets out the main functional groups of professional competencies in their preparation.
Keywords: professional competencies; masters-agronomists in selective breeding and genetics; professional training